Porous carbon material with high electrochemical performance as well as preparation method and application of porous carbon material

By using a porous carbon material prepared by reacting polyurethane resin with components such as high carbon hybrids, the problems of low carbon yield and poor electrochemical performance in the prior art are solved, and energy storage electrode materials with high energy density and long cycle life are achieved.

CN119833320APending Publication Date: 2025-04-15WANHUA CHEMYANTAI RONGWEI POLYURETHANE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510000299.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing porous carbon-based energy storage electrode materials have low carbon yield and poor electrochemical performance, making it difficult to meet the needs of high energy density, high power density and long cycle life.

Method used

Polyurethane resin is used as a precursor to prepare porous carbon materials by reacting with components such as high-carbon hybrids, catalysts, and surfactants, and improve carbon yield and electrochemical properties through carbonization treatment.

Benefits of technology

It achieves high carbon yield and excellent electrochemical performance, and is suitable for supercapacitor electrode materials, with high specific capacitance, good rate performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224779360000021
    Figure BDA0005224779360000021
  • Figure BDA0005224779360000071
    Figure BDA0005224779360000071
  • Figure BDA0005224779360000072
    Figure BDA0005224779360000072
Patent Text Reader

Abstract

The invention discloses a porous carbon material with high electrochemical performance as well as a preparation method and application thereof. A high-carbon hybrid with a high-temperature-resistant structure and heteroatoms is introduced into polyurethane resin molecules, and after heat treatment, the final carbon material is endowed with relatively high carbon yield and electrochemical performance. The high-yield carbon material has good conductivity and extremely high specific surface area, can be directly used as a flexible supercapacitor electrode, and has higher specific capacitance, good rate capability and cycling stability. The treatment method has the advantages of simple and easy process, wide raw material source and low cost, successfully solves the problems of low yield and low electrochemical performance of the current carbon-based energy storage material, and accords with the environment-friendly design concept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a porous electrode material and a preparation method and application thereof. Background Art

[0002] In order to reduce the use of petroleum fuels and reduce carbon dioxide emissions, many countries have increased their research and investment in hybrid electric vehicles and electric vehicles. The most critical part of hybrid electric vehicles and electric vehicles is the power system, so it is particularly important to develop efficient energy storage devices with high energy density, high power density, long cycle life, low cost, good safety performance and environmental friendliness.

[0003] Among the numerous energy storage electrode materials, the porous carbon-based three-dimensional network structure has attracted widespread attention with its excellent conductivity, high specific surface area, and excellent electrochemical stability, and has become a research hotspot in this field. More importantly, due to the spatiality of the carbon-based three-dimensional network structure, it can be directly used as a flexible electrode material for energy storage devices, thereby expanding the application field of energy storage devices. The preparation of porous carbon-based materials usually requires a carbon precursor. After a special heat treatment, the precursor is obtained to obtain a carbon-based material. General precursors include: asphalt, phenolic resin, polyurethane, biomass materials, etc. The carbon content, structural temperature resistance, heteroatom content, etc. of the precursor directly affect the final carbon yield and electrochemical performance.

[0004] Therefore, how to obtain porous three-dimensional carbon materials with a simple method, high carbon yield and large specific surface area is of great significance. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a porous carbon material with polyurethane resin as a precursor and a preparation method thereof. The porous carbon material preparation method is simple, has a high carbon yield, and the obtained product has a large specific surface area and excellent electrical properties.

[0006] Another object of the present invention is to provide an application of the above-mentioned porous carbon material, which can be used for supercapacitor electrode materials and has high specific capacitance, good rate performance and cycle stability as an electrode.

[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a porous carbon material prepared using a polyurethane resin as a precursor; the polyurethane resin is prepared by reacting a component A and a component B; the mass ratio of the component A to the component B is 1.6-2.5:1, for example, 1.6:1, 1.8:1, 2.0:1, 2.2:1, 2.4:1, 2.5:1, etc., preferably 1.6-2.3:1;

[0009] Wherein, the component A is isocyanate,

[0010] The B component is a composite polyether, and its mass percentage composition, based on the total mass of the B component, includes:

[0011] Polyol combination 57-94wt%, such as 57wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 94wt%, preferably 65-80wt%,

[0012] High carbon hybrid 5-20wt%, such as 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, preferably 6-15wt%,

[0013] Water 0.1-6wt%, for example 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, preferably 1-5wt%

[0014] Catalyst 0.1-6wt%, such as 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, preferably 1-5wt%,

[0015] Surfactant 0.1-11wt%, for example 0.1wt%, 1wt%, 3wt%, 5wt%, 7wt%, 9wt%, 11wt%, preferably 1-10wt%.

[0016] In a specific embodiment, in the combined polyether of component B, the high-carbon hybrid is a hydroxyl compound selected from the condensation product of an epoxy compound, a polyaniline compound, and a triazole compound.

[0017] Preferably, the epoxy compound is a compound having two epoxy groups, preferably an aliphatic diglycidyl ether, such as a diglycidyl ether having 2-8 carbon atoms on the main chain except for the epoxy group, including but not limited to one or more of diglycidyl ether, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, butanediol diglycidyl ether, and pentaerythritol diglycidyl ether.

[0018] Preferably, the polyaniline compound is selected from dianiline compounds, including but not limited to one or more of benzidine, N-phenylaniline, bis(3,4-xylyl)amine, salicylanilide, and 4-methyl-[1,1-biphenyl]-4-amine.

[0019] Preferably, the triazole compound is selected from one or more of 1,2,4-triazole, 1,2,3-triazole, and benzotriazole, preferably a triazole compound containing a benzene ring, such as benzotriazole.

[0020] In a preferred example, the molecular weight of the high carbon hybrid is 450-550, and the hydroxyl value is 200-350 mg KOH / g.

[0021] In a preferred example, the high carbon hybrid has a structure as shown in Formula 1:

[0022]

[0023] Wherein, -R' is a structure derived from a polyaniline compound; -R" is a structure derived from a triazole compound; -R- represents -O- or -O-X-O-, wherein X is a C1-C6 alkyl group.

[0024] In a preferred example, the high carbon hybrid is prepared by mixing an epoxy compound, a polyaniline compound and a triazole compound, wherein the mixing molar ratio of the epoxy compound, the polyaniline compound and the triazole compound is 1-2:0.5-1:0.5-1;

[0025] Wherein, the reaction temperature is 35-60°C and the reaction time is 4-8h;

[0026] The above method for preparing a polycondensate from epoxy compounds, polyaniline compounds and triazole compound monomers is an existing process. In specific applications, in addition to the conditions specified above, other related operations and process conditions actually used, and the devices used, can be carried out using the corresponding conventional selections in the art, and the present invention will not be repeated here.

[0027] The high-carbon hybrid in the component B combined polyether of the present invention has a highly heat-resistant benzene ring structure and abundant nitrogen atoms. It is introduced into a polyurethane resin as a precursor for preparing a porous carbon material. After carbonization treatment, the highly heat-resistant benzene ring structure gives the carbon material a high carbon yield, and the abundant nitrogen atoms are in situ introduced into the carbon material lattice as heteroatoms. The redox reaction of the heteroatoms during the charge and discharge process can increase the pseudocapacitance of the carbon material, further improving the electrochemical performance.

[0028] In a specific embodiment, in the polyurethane resin raw material, the isocyanate index (R value) of component A and component B is 1.5-2.5, such as 1.5, 1.8, 2.0, 2.2, 2.5, etc., preferably 1.6-2.3. The isocyanate index is the molar ratio of the isocyanate group contained in component A to the hydroxyl group contained in component B.

[0029] In one specific embodiment, the isocyanate in component A is selected from polyisocyanates with NCO functionality ≥ 2, preferably one or more aromatic diisocyanates, more preferably polymethylene polyphenyl polyisocyanate;

[0030] Preferably, the viscosity of the polymethylene polyphenyl polyisocyanate is 130-800 mPa·s (25° C.), and more preferably, the polymethylene polyphenyl polyisocyanate includes but is not limited to PM-200, PM-400, PM-700, PM-2010 and other brands of Wanhua Chemical.

[0031] In a specific embodiment, in the B component combination polyether, the polyol combination includes one or more of polyester polyol and polyether polyol.

[0032] In a preferred example, the polyol combination comprises the following components:

[0033] Polyester polyol, number average molecular weight of 200-1000, preferably 300-800, functionality of 2-3, hydroxyl value of 200-800 mgKOH / g;

[0034] Polyether polyol A, number average molecular weight of 200-900, preferably 250-900, functionality of 4-8, hydroxyl value of 250-800 mgKOH / g;

[0035] Polyether polyol B has a number average molecular weight of 500-3000, preferably 700-2000, a functionality of 2-3, and a hydroxyl value of 50-330 mgKOH / g.

[0036] Specifically, as a preferred embodiment, the mass percentage of each component in the polyol combination is as follows:

[0037] Polyester polyol, 60-86wt%, such as 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 86wt%, etc., preferably 65-78wt%;

[0038] Polyether polyol A, 10-30wt%, for example 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, etc., preferably 15-25wt%;

[0039] Polyether polyol B, 0-24wt%, such as 0wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 24wt%, etc., preferably 2-18wt%.

[0040] Specifically, as a preferred embodiment, the polyester polyol is a condensation product of a diol and a dicarboxylic acid (anhydride); preferably, the acid (anhydride) is one or more of phthalic acid (anhydride), isophthalic acid (anhydride), terephthalic acid, adipic acid (anhydride), glutaric acid (anhydride) and succinic acid (anhydride), more preferably one or more of phthalic acid (anhydride), adipic acid (anhydride) and terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol, butanediol, pentanediol and hexanediol, preferably diethylene glycol and / or dipropylene glycol.

[0041] Specifically, as a preferred embodiment, the polyether polyol A is a polyether polyol with one or more of sucrose, sorbitol, xylitol, pentaerythritol and mannitol as initiators, and the initiator is preferably one or more of sucrose, sorbitol and pentaerythritol, and more preferably one or more of sucrose and sorbitol.

[0042] Specifically, as a preferred embodiment, the polyether polyol B is a polyether polyol with one or more of glycerol, diethylene glycol, ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol and trimethylolpropane as an initiator, and the initiator is preferably one or more of glycerol, ethylene glycol, propylene glycol and diethylene glycol, and more preferably one or more of glycerol and propylene glycol.

[0043] In a specific embodiment, in the B component combined polyether, the catalyst is selected from one or more of tertiary amine catalysts and organometallic catalysts;

[0044] Preferably, the tertiary amine catalyst is selected from one or more of pentamethyldiethylenetriamine, pentamethyldipropylenetriamine, N-methylimidazole, N,N-dimethylcyclohexylamine, triethylenediamine, 1,4-dimethylpiperazine, N,N-dimethylbenzylamine, N,N-dimethyl(hexadecyl)amine, di(dimethylaminoethyl)ether, and triethanolamine; more preferably, one or more of triethylenediamine, di(dimethylaminoethyl)ether, N,N-dimethylcyclohexylamine, pentamethyldiethylenetriamine, pentamethyldipropylenetriamine, and N,N-dimethylbenzylamine;

[0045] Preferably, the organometallic catalyst is selected from one or more of organotin compounds and potassium carboxylate compounds, more preferably one or more of potassium isooctanoate, potassium acetate, potassium formate, dibutyltin dilaurate, tetrabutyl titanate, zinc isooctanoate, stannous octoate and potassium oleate.

[0046] In a specific embodiment, in the B component combined polyether, the surfactant includes one or more of non-silicon compounds and polyether-modified organic silicon compounds, preferably one or more of polyether-modified organic silicon compounds. The surfactant can increase the mutual solubility of the raw materials, and has the functions of emulsifying foam materials, stabilizing foam and regulating pores.

[0047] According to the porous carbon material described above, its macroscopic size is 1 mm-1 m; its interior is a porous structure with a pore size range of 0.2 nm-0.5 cm and a specific surface area of ​​100-2800 m 2 g -1 .

[0048] The porous carbon material of the present invention has a total content of carbon, oxygen and hydrogen elements of ≥99.9wt%, and preferably, has an oxygen content of 0.1-20wt%.

[0049] In a second aspect, the present invention provides a method for preparing the porous carbon material, which includes the steps of preparing a polyurethane resin precursor by reacting the isocyanate of component A and the polyether of component B, and preparing the porous carbon material by carbonizing the polyurethane resin precursor.

[0050] The above two steps are both known processes disclosed in the prior art. In actual use, the relevant operations and process conditions in the preparation method of the present invention, and the devices used therein, can be carried out by the corresponding conventional selections in the art. There is no particular limitation on this. Technicians can optimize the known processes in the prior art according to actual needs.

[0051] Specifically, a method for preparing a porous carbon material comprises the following steps:

[0052] (1) uniformly mixing a polyol combination with a high carbon hybrid, a catalyst, a surfactant, and water to obtain a combined polyether;

[0053] (2) pouring the combined polyether and isocyanate obtained in step (1) into a mold through a high-pressure foaming machine to obtain a polyurethane resin precursor;

[0054] (3) The polyurethane resin precursor obtained in step (2) is placed in an inert protective gas and calcined at a high temperature to obtain the porous carbon material.

[0055] Wherein, the mass ratio of the isocyanate to the combined polyether in step (2) is 1.6-2.5:1.

[0056] Wherein, the casting process in step (2) is a casting process well known to those skilled in the art;

[0057] Preferably, the temperature of the isocyanate and the combined polyether is controlled at 22-26°C, and the mold temperature is controlled at 35-55°C.

[0058] Wherein, the inert protective gas in step (3) is selected from one or more of nitrogen, argon and helium, preferably nitrogen.

[0059] Wherein, the heating rate of step (3) is 2-10°C / min, the calcination temperature is 800-1600°C, the calcination time is 0.5-24h, and the temperature is naturally cooled to room temperature after calcination;

[0060] Specifically, after the calcination at elevated temperature in step (3), conventional post-treatment methods such as water washing and drying are also included. One specific operation is to soak in deionized water for two days to remove surface residues, and then dry in an oven to obtain the carbon material.

[0061] In the preparation method of the present invention, the carbon yield after the temperature-raising calcination heat treatment in step (3) can reach more than 40%.

[0062] In a third aspect, the present invention provides applications of the porous carbon material.

[0063] The porous carbon material of the present invention has high electrochemical performance and can be used to prepare nano-scale composite electrode materials, including one or more of carbon materials (such as carbon fiber, graphene, carbon nanotubes, etc.), metal oxides, conductive polymers, etc.

[0064] The above materials can all be used as electrode materials for supercapacitors, either alone or in combination with other electrode materials.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] The present invention introduces a high-carbon hybrid with a high-temperature resistant structure and heteroatoms into a polyurethane resin molecule as a carbon material precursor, and after heat treatment, gives the final carbon material a higher carbon yield and electrochemical performance. The carbon material has good conductivity and extremely high specific surface area, can be directly used as a flexible supercapacitor electrode, and has higher specific capacitance, good rate performance and cycle stability.

[0067] This treatment method is simple and easy to operate, with a wide range of raw materials and low cost. It successfully solves the current problems of low yield and low electrochemical performance of carbon-based energy storage materials, and is in line with the environmentally friendly design concept. DETAILED DESCRIPTION

[0068] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0069] The following descriptions of the instruments used for the detection in the comparative examples are as follows:

[0070] Total specific surface area and average pore size: The instrument is a fully automatic specific surface area and pore size distribution analyzer, model: Autosorb-iQ2, and the instrument manufacturer is Quantachrome Company of the United States.

[0071] Capacitance: The instrument is an electrochemical workstation, model CHI 660C, manufactured by Shanghai Chenhua Instrument Company.

[0072] The sources of the raw materials used in the following examples and comparative examples are described as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:

[0073] Polyester polyol: polyester polyol DM-2004 (molecular weight 460, functionality 2, hydroxyl value 240 mg KOH / g, terephthalic acid polyester polyol) produced by Beijing Demeishichuang Co., Ltd., polyester polyol PS-3152 (molecular weight 350, functionality 2, hydroxyl value 315 mg KOH / g, phthalic anhydride polyester polyol) produced by Stepan Company;

[0074] Sorbitol polyether (polyether polyol A): Wanhua Chemical R6245 (molecular weight 730, functionality 6, hydroxyl value 460 mgKOH / g, sorbitol as initiator, PO as repeating unit);

[0075] Polyoxypropylene triol (polyether polyol B): Wanhua Chemical S3007 (molecular weight 700, functionality 3, hydroxyl value 240 mgKOH / g, glycerol as initiator, PO as repeating unit);

[0076] Epoxides: diglycidyl ether from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., butanediol diglycidyl ether from Suzhou Senfida Chemical Co., Ltd.;

[0077] Dianiline chemicals: salicylanilide from Hubei Xinghengye Technology Co., Ltd., bis(3,4-xylyl)amine from Yurui (Shanghai) Chemical Co., Ltd.;

[0078] Triazole compounds: De-Benzotriazole from DeLan Chemical Co., Ltd.;

[0079] High carbon hybrid-1: a trihydroxy compound obtained by reacting diglycidyl ether, salicylanilide and benzotriazole in a molar ratio of 1:1:1, the reaction temperature is 55°C, the reaction time is 7h, the molecular weight is 461, the hydroxyl value is 365mg KOH / g, and the structural formula is:

[0080]

[0081] High carbon hybrid-2: a dihydroxy compound obtained by reacting butanediol diglycidyl ether, bis(3,4-xylyl)amine and benzotriazole in a molar ratio of 1:1:1, with a reaction temperature of 45°C and a reaction time of 6h, a molecular weight of 546, a hydroxyl value of 205mg KOH / g, and a structural formula of:

[0082]

[0083] Surfactant: Momentive L-6900 silicone oil;

[0084] Catalyst: Evonik Chemicals Dabco5, DabcoK15;

[0085] Polymethylene polyphenyl isocyanate: Wanhua Chemical PM-400;

[0086] Acetylene black: battery grade, Shenzhen BAK Battery Co., Ltd.;

[0087] Nickel foam: purity 99.99%, Tianyu Technology Development Co., Ltd.;

[0088] Polytetrafluoroethylene: purity 99.99%, Aldrich.

[0089] Example 1

[0090] Preparation of component B: add 30kg PS-3152, 22kg DM-2004, 15kg R6245, 7kg S3007, 5kg high carbon hybrid-1, 5kg high carbon hybrid-2, 9kg L-6900, 3kg Dabco5, 2kg DabcoK15, and 2kg water into a 100L kettle, stir and disperse for 60min to obtain component B.

[0091] Preparation of polyurethane resin precursor: Add component A PM-200 and component B to the storage tank of KraussMaffei high-pressure casting machine, preheat the material temperature and the mold to 25°C, and pour the foam into a horizontal mold according to the mass ratio of component A: component B = 2.0:1. After the foam is matured for 24 hours, the polyurethane resin precursor is obtained.

[0092] The polyurethane resin precursor was cut into a fixed shape suitable for the size of the tube furnace, and its mass was 200 mg. The polyurethane resin precursor was placed in a porcelain boat, which was placed in a tube furnace and heated at 5 °C min under a nitrogen atmosphere. -1 The temperature was raised to 1000℃ and calcined for 2h, then cooled to room temperature naturally. After being taken out, it was soaked in deionized water for two days to remove surface residues, and then kept in an oven at 90℃ for 12h to obtain the final porous carbon material. The carbon yield was 47% after the mass calculation before and after.

[0093] Example 2-3

[0094] According to the types and amounts of raw materials in Table 1, the operation of Example 1 was repeated to prepare the porous carbon materials of Examples 2 and 3, respectively.

[0095] Table 1 Types and amounts of raw materials used in Examples 1-3 (mass, kg)

[0096]

[0097]

[0098] Comparative Example 1

[0099] The carbon material was prepared according to the method of Example 1, except that high carbon hybrid-1 and high carbon hybrid-2 were not added to component B, and other operations and conditions remained unchanged.

[0100] Comparative Example 2

[0101] Referring to the above-mentioned high carbon hybrid-1 method, a condensate is prepared by reacting diglycidyl ether and salicylanilide in a molar ratio of 1:1.

[0102] The carbon material was prepared according to the method of Example 1, except that the high carbon hybrid-1 and high carbon hybrid-2 in component B were replaced by an equal amount of the above condensate of this comparative example, and other operations and conditions remained unchanged.

[0103] Comparative Example 3

[0104] Referring to the above-mentioned high carbon hybrid-1 method, a condensate is prepared by reacting diglycidyl ether with benzotriazole in a molar ratio of 1:1.

[0105] The carbon material was prepared according to the method of Example 1, except that the high carbon hybrid-1 and high carbon hybrid-2 in component B were replaced by an equal amount of the above condensate of this comparative example, and other operations and conditions remained unchanged.

[0106] Comparative Example 4

[0107] Referring to the above-mentioned high carbon hybrid-1 method, a condensate is prepared by reacting salicylanilide and benzotriazole in a molar ratio of 1:1.

[0108] The carbon material was prepared according to the method of Example 1, except that the high carbon hybrid-1 and high carbon hybrid-2 in component B were replaced by an equal amount of the above condensate of this comparative example, and other operations and conditions remained unchanged.

[0109] The carbon yield, total specific surface area and average pore size of the porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-4 were tested. The test results are shown in Table 2.

[0110] The electrochemical performance of the porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-4 was tested. The test results are shown in Table 2. The method is as follows:

[0111] Take 2 mg of porous carbon material matrix and place it in two pieces of nickel foam as working electrode, metal Pt as counter electrode, Hg / HgO electrode as reference electrode, electrolyte is 6M KOH, charge and discharge cut-off voltage is -1-0V, when charge and discharge current is 0.1A -1 When the specific capacity is tested.

[0112] Table 2 Performance test results of porous carbon materials prepared in Example 2

[0113]

[0114] The charge and discharge cut-off voltage of the above test is -1 to 0 V. The specific capacitance is tested at a current density of 0.1 A / g, and the cycle stability refers to the retention rate of the specific capacitance after 10,000 charge and discharge cycles at 0.1 A / g.

[0115] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A porous carbon material, characterized in that: The polyurethane resin is prepared by reacting component A and component B; the mass ratio of component A to component B is 1.6-2.5:1, preferably 1.6-2.3:1; Wherein, the component A is isocyanate, The B component is a composite polyether, and its mass percentage composition, based on the total mass of the B component, includes:

2. The porous carbon material according to claim 1, characterized in that The high carbon hybrid is a hydroxy compound selected from the condensation product of epoxy compounds, polyaniline compounds and triazole compounds; Preferably, the epoxy compound is a compound having two epoxy groups, preferably aliphatic diglycidyl ether, more preferably a diglycidyl ether having 2-8 carbon atoms in the main chain except for the epoxy group, further preferably one or more of diglycidyl ether, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, butanediol diglycidyl ether, and pentaerythritol diglycidyl ether; Preferably, the polyaniline compound is selected from dianiline compounds, preferably one or more of benzidine, N-phenylaniline, bis(3,4-xylyl)amine, salicylanilide, and 4-methyl-[1,1-biphenyl]-4-amine; Preferably, the triazole compound is selected from one or more of 1,2,4-triazole, 1,2,3-triazole, and benzotriazole, preferably a triazole compound containing a benzene ring, and more preferably a benzotriazole substance; and / or The high carbon hybrid is prepared by a mixed reaction of an epoxy compound, a polyaniline compound and a triazole compound; Preferably, the mixing molar ratio of the epoxy compound, the polyaniline compound and the triazole compound is 1-2:0.5-1:0.5-1; Preferably, the reaction temperature is 35-60°C and the reaction time is 4-8h.

3. The porous carbon material according to claim 1 or 2, characterized in that: The molecular weight of the high carbon hybrid is 450-550, and the hydroxyl value is 200-350 mg KOH / g; and / or The high carbon hybrid has a structure as shown in Formula 1: Wherein, -R' is a structure derived from a polyaniline compound; -R" is a structure derived from a triazole compound; -R- represents -O- or -O-X-O-, wherein X is a C1-C6 alkyl group.

4. The porous carbon material according to any one of claims 1 to 3, characterized in that: The isocyanate index of component A and component B is 1.5-2.5, preferably 1.6-2.3; and / or The isocyanate in component A is selected from polyisocyanates with NCO functionality ≥ 2, preferably one or more aromatic diisocyanates, more preferably polymethylene polyphenyl polyisocyanate; Preferably, the viscosity of the polymethylene polyphenyl polyisocyanate is 130-800 mPa·s. More preferably, the polymethylene polyphenyl polyisocyanate is selected from PM-200, PM-400, PM-700 and PM-2010 of Wanhua Chemical.

5. The porous carbon material according to any one of claims 1 to 4, characterized in that: The polyol combination includes one or more of polyester polyols and polyether polyols; Preferably, the polyol combination comprises the following components: Polyester polyol, number average molecular weight of 200-1000, preferably 300-800, functionality of 2-3, hydroxyl value of 200-800 mgKOH / g; Polyether polyol A, number average molecular weight of 200-900, preferably 250-900, functionality of 4-8, hydroxyl value of 250-800 mgKOH / g; Polyether polyol B has a number average molecular weight of 500-3000, preferably 700-2000, a functionality of 2-3, and a hydroxyl value of 50-330 mgKOH / g. Preferably, the mass percentage of each component in the polyol combination is as follows: Polyester polyol, 60-86wt%, preferably 65-78wt%; Polyether polyol A, 10-30wt%, preferably 15-25wt%; Polyether polyol B, 0-24wt%, preferably 2-18wt%.

6. The porous carbon material according to claim 5, characterized in that ,, the polyester polyol is a condensation product of a diol and a dicarboxylic acid (anhydride); preferably, the acid (anhydride) is one or more of phthalic acid (anhydride), isophthalic acid (anhydride), terephthalic acid, adipic acid (anhydride), glutaric acid (anhydride) and succinic acid (anhydride), more preferably one or more of phthalic acid (anhydride), adipic acid (anhydride) and terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol, butanediol, pentanediol and hexanediol, preferably diethylene glycol and / or dipropylene glycol; and / or The polyether polyol A is a polyether polyol with one or more of sucrose, sorbitol, xylitol, pentaerythritol and mannitol as an initiator, wherein the initiator is preferably one or more of sucrose, sorbitol and pentaerythritol, and more preferably one or more of sucrose and sorbitol; and / or The polyether polyol B is a polyether polyol with one or more of glycerol, diethylene glycol, ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol and trimethylolpropane as an initiator, and the initiator is preferably one or more of glycerol, ethylene glycol, propylene glycol and diethylene glycol, and more preferably one or more of glycerol and propylene glycol.

7. The porous carbon material according to any one of claims 1 to 6, characterized in that: The catalyst is selected from one or more of tertiary amine catalysts and organic metal catalysts; Preferably, the tertiary amine catalyst is selected from one or more of pentamethyldiethylenetriamine, pentamethyldipropylenetriamine, N-methylimidazole, N,N-dimethylcyclohexylamine, triethylenediamine, 1,4-dimethylpiperazine, N,N-dimethylbenzylamine, N,N-dimethyl(hexadecyl)amine, di(dimethylaminoethyl)ether, and triethanolamine; more preferably, one or more of triethylenediamine, di(dimethylaminoethyl)ether, N,N-dimethylcyclohexylamine, pentamethyldiethylenetriamine, pentamethyldipropylenetriamine, and N,N-dimethylbenzylamine; Preferably, the organometallic catalyst is selected from one or more of organotin compounds and potassium carboxylate compounds, more preferably one or more of potassium isooctanoate, potassium acetate, potassium formate, dibutyltin dilaurate, tetrabutyl titanate, zinc isooctanoate, stannous octoate and potassium oleate; and / or The surfactant includes one or more of non-silicon compounds and polyether-modified organic silicon compounds, preferably one or more of polyether-modified organic silicon compounds.

8. A method for preparing the porous carbon material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) uniformly mixing a polyol combination with a high carbon hybrid, a catalyst, a surfactant, and water to obtain a combined polyether; (2) pouring the combined polyether and isocyanate obtained in step (1) into a mold through a high-pressure foaming machine to obtain a polyurethane resin precursor; (3) The polyurethane resin precursor obtained in step (2) is placed in an inert protective gas and calcined at a high temperature to obtain the porous carbon material.

9. The preparation method according to claim 8, characterized in that: The mass ratio of the isocyanate to the combined polyether in step (2) is 1.6-2.5:1; and / or In the casting process of step (2), the temperature of the isocyanate and the combined polyether is controlled at 22-26° C., and the mold temperature is controlled at 35-55° C.; and / or The inert protective gas in step (3) is selected from one or more of nitrogen, argon and helium, preferably nitrogen; and / or Wherein, in step (3), the heating rate of the calcination is 2-10°C / min, the calcination temperature is 800-1600°C, and the calcination time is 0.5-24h.

10. Use of the porous carbon material according to any one of claims 1 to 7 or the porous carbon material prepared by the method according to claim 8 or 9 in the field of electrode materials, preferably for preparing nano-scale composite electrode materials, such as carbon materials, metal oxides, and conductive polymers.